El proceso de comunicación y su impacto en el proceso educativo en las instituciones de educación básica - Herrera Silva, Fernando Javier (Machala, 2019)
Human communication is an inherent process in every society, it is mediated by specific elements such as the language that is source for understanding between people. In Basic Education the communication that is provided in the classroom through pedagogical dialogue not always has been adequate on the part of the teacher for a good development in academic relations with their students, which means a determining factor in the construction of a welcoming environment, in the participation of students, socialization of knowledge, in addition to motivation and acquisition of meaningful learning. In the course of this essay, mention is made of the communication process and its impact on the educational process, to improve the interaction between teachers and apprentices thus a better coexistence to develop learnings, from which the meanings of communication and language, pedagogical dialogue, describes communication in the negative aspect within aulic experiences, as well as the positive aspect as a communicative competence of the teacher, the role of language within learning significant, in addition to the characteristics for successful teaching communication. The methodology used is the literature of documented review, qualitative and explanatory, is oriented under the theoretical approach of communicative action developed by Habermas, taking into account the argumentation in the use of language for the development of cognitive skills, finally a guide to assertive communication recommendations is generated to optimize the interaction of teaching-students in the acquisition of meaningful learnings.
La comunicación humana es un proceso inherente en toda sociedad, se media por elementos específicos como el lenguaje que es fuente para la comprensión entre personas. En Educación Básica la comunicación que se brinda en las aulas por medio del diálogo pedagógico no siempre ha sido la adecuada de parte del docente para un buen desarrollo en las relaciones académicas con sus alumnos, lo que significa un factor determinante en la construcción de un ambiente acogedor, en la participación de los estudiantes, socialización de saberes, además para la motivación y adquisición de aprendizajes significativos. En el transcurso de este ensayo se hace mención al proceso de comunicación y su impacto en el proceso educativo, para mejorar la interacción entre docente y aprendices por ende una mejor convivencia para desarrollar aprendizajes, del cual se analiza los significados de comunicación y lenguaje, diálogo pedagógico, se describe la comunicación en el aspecto negativo dentro de las experiencias áulicas, así también el aspecto positivo como competencia comunicativa del docente, la función del lenguaje dentro del aprendizaje significativo, además las características para una acertada comunicación docente. La metodología que se utiliza es la bibliográfica de revisión documentada, de carácter cualitativo y de tipo explicativo, se orienta bajo el enfoque teórico de la acción comunicativa desarrollado por Habermas, tomando en cuenta la argumentación en el uso del lenguaje para el desarrollo de habilidades cognitivas, por último se genera una guía de recomendaciones comunicacionales asertivas para optimizar la interacción docente- estudiantes en la adquisición de aprendizajes significativos.
Keywords: COMMUNICATION PROCESS; PEDAGOGICAL DIALOGUE; LANGUAGE; EDUCATIONAL PROCESS